Performance Investigation of Boost Converter Based on Fuzzy Logic Using Mamdani Rules - Muamalah, Khairul; Wiryajati, I Ketur; Satiawan, I Nyoman Wahyu (CV. Publikasi Indonesia, 2024)
Boost Converter is one type of DC converter that is often used for various purposes where the output voltage is equal to or higher than the input voltage. To get an output voltage higher than the input voltage commonly used by electrical and electronic equipment, a voltage increase is needed that can be varied as needed. One way to increase the voltage with a variable is to use the Boost Converter with Fuzzy Logic control. This research proposes a Boost Converter that can increase the variable direct voltage. Boost Converter proposed Fuzzy Logic using Mamdani's rules as a controller. Boost Converter is investigated on Open Jacks Boost Converter, Closed Loop Boost Converter and Boost Converter Fuzzy Logic Control Duty cycle on Boost converters using PID and Fuzzy Logic implemented using Simulink Matlab. The results of the investigation show that the Boost Converter designed in this study has worked well according to the purpose.